Development of a 3d Visco-Elastic Model for Wood Under Large Deformations - Saavedra-Flores, E; Yanez-Cart, S; Guzman-Inostroza, C; Pina, J (Scipedia S.L., 2022)
Some of the most frequently observed phenomena in structural materials are creep and relaxation. Both are associated with time-dependent behavior and dissipative rheological variables. In the case of wood, long-term creep can produce excessive deformation and instability problems by magnifying short-term deflections. Also, wood presents changes in its mechanical properties due to its hygroscopy, so that moisture appears as an important parameter to be considered. A priori, it is known that the moisture content in wood cells and the angle of microfibrils are parameters that directly affect the overall cell stiffness. With this information, material physics hypotheses can be elaborated to develop a constitutive model in large deformations to predict phenomena such as creep and relaxation in the medium and/or long term. The microstructure of the cell wall can be represented through a model of fiber-reinforced composite material originally developed for biomaterials such as arteries and fibrous tissues. Where the anisotropic character is conferred by the distribution of the fibers within the isotropic matrix of the material. This work aims to adapt these models to represent the mechanical behavior of the wood cell with faithful representation of its microstructure. FEniCS is used for the numerical implementation of the material. In this paper the validations, current status, conclusions, and perspectives of this research are presented. © 2022, Scipedia S.L. All rights reserved.